A interface da arte e do bem-estar na promoção da saúde na terceira idade - Vasques, Márcia Camargo Penteado Corrêa Fernandes [UNESP] (2014)
The artistic manifestations may contribute to health promotion, encouraging expression of feelings, sensations and perceptions because of the release of stiffness and imprisonments that manifest as disease. The present study, conducted with elderly, in Botucatu / SP, aimed to develop and validate a theoretical model representing the experiences of these elderly people with art, lifelong, enabling the understanding of experiences with art, and its contribution for the state of personal and collective well-being to influence Public Health Policies, supporting the effective exercise of this practice in promoting physical and mental health. Data were collected through unstructured type of focused and recorded on digital system interviews. 07 persons aged 60 years and over were interviewed. The methodological framework used was the Grounded Theory and Symbolic Interactionisn theoretical framework. Analysis of the data revealed three phenomena: THE ARTISTIC BACKGROUND TO FINDING A FAVORABLE; DEVELOPING EMOTIONS THROUGH ART, ART AS A TRANSFORMER ELEMENT